Polyvinyl pyrrolidone-chitosan blend membrane for pervaporation separation of trimethyl boratemethanol mixture - Ozekmekci, Mehtap; Copur, Mehmet; Unlu, Derya (Springer, 2025)
Trimethyl borate (TMB) is an essential chemical for applications ranging from organic synthesis to borohydride production and requires efficient separation from methanol for optimal utilization. This study investigates the pervaporation performance of blend membranes composed of different ratios of chitosan (CS) and polyvinyl pyrrolidone (PVP) to improve the separation of TMB/methanol mixtures through pervaporation. The structural morphology, thermal properties, and crystalline nature of these membranes were comprehensively characterized using Fourier transform infrared spectroscopy, thermogravimetric analysis, contact angle measurements, scanning electron microscopy, and X-ray diffraction analysis. Pervaporation experiments were conducted by varying feed compositions, operating temperatures, and PVP ratios. The results demonstrated that increasing PVP content has a significant effect on permeation flux. The best conditions were obtained at 45 degrees C of operation temperature and 75% (by wt) TMB-25% (by wt) methanol mixture by utilizing a PVP-CS-2 membrane, recording flux value of 335.44 g/m2 h. Additionally, PVP-CS-1 and PVP-CS-2 blend membranes were subjected to a crosslinking process to evaluate their separation performance. The crosslinked PVP-CS-1 membrane showed a good performance, with a selectivity value of 146.37. Additionally, the crosslinked PVP-CS-2 membrane exhibited remarkable stability 5 run experiments, indicating strong chemical and mechanical endurance.
Keywords: Trimethyl borate; Azeotrope; Pervaporation; Chitosan; Polyvinyl pyrrolidone